Multiple spin-orbit excitons in α-RuCl3 from bulk to atomically thin layers - Je-Ho Lee (Nature Portfolio, 2021)
Abstract The van der Waals Kitaev magnet α-RuCl3 has recently garnered considerable attention due to its possible realization of topological spin liquids. Combining Raman spectroscopy with numerical calculations, we report here the thickness dependence of electronic structure and ensuing low-energy excitations for exfoliated α-RuCl3. We observe two pronounced peaks at A1 = 249 meV and A2 = 454 meV, which are assigned to single and double spin-orbit (SO) excitons, respectively. Our numerical calculations support this interpretation by reproducing their spectral energy and shape with the electronic parameters: SO coupling λ = 140 meV, Hund’s coupling J H = 350 meV, and on-site Coulomb interaction U = 2.35 eV. The multiple SO excitons persist down to a single layer, whereas their peaks shift slightly to lower energy. For frequencies below 350 cm−1, both a magnetic continuum and phonons show noticeable thickness dependence. These results demonstrate that a SO entangled j eff = 1/2 picture remains valid in a monolayer limit despite the presence of lattice distortions.